Enrichment of Microbial Consortium with Hydrogenotrophic Methanogens for Biological Biogas Upgrade to Biomethane in a Bubble Reactor under Mesophilic Conditions - Spyridonidis, Apostolos; Vasiliadou, Ioanna A.; Stathopoulou, Panagiota; Tsiamis, Athanasios; Tsiamis, George; Stamatelatou, Katerina (Sustainability, 2023)
The biological upgrading of biogas to simulate natural gas properties contributes to the sustainable establishment of biogas technology. It is an alternative technology to the conventional physicochemical methods applied in biomethane plants and has been studied mainly in thermophilic conditions. Developing an enriched culture for converting the CO2 of biogas to CH4 in mesophilic conditions was the subject of the present study, which could facilitate the biological process and establish it in the mesophilic range of temperature. The enrichment took place via successive dilutions in a bubble bioreactor operated in fed-batch mode. The methane percentage was recorded at 95.5 ± 1.2% until the end of the experiment. The methane production rate was 0.28–0.30 L L−1 d−1 following the low hydrogen loading rate (1.2 ± 0.1 L L−1 d−1) applied to avoid acetate accumulation. Hydrogenotrophic methanogens, Methanobrevibacter sp., were identified at a proportion of 97.9% among the Archaea and 60% of the total population of the enriched culture. Moreover, homoacetogens (Sporomusa sp.) and acetate oxidizers (Proteiniphilum sp.) were also detected, indicating that a possible metabolic pathway for CH4 production from CO2 is via homoacetogenesis and syntrophic acetate oxidation, which kept the acetate concentration at a level of 143 ± 13 mg L−1. It was found that adding NaHCO3 was adequate to sustain the pH at 8.25.